Uji aktivitas antioksidan ekstrak etanol dan sari kulit nanas (Ananas comosus (L) Merr) menggunakan metode radical scavenger - Nadia, Syarifah; Julianty, Siti Muliani; Tambunan, Ika Julianti; Fujiko, Muflihah (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Inheritance, Indonesian society has been utilizing various plants as traditional medicine for preventive measures and treatment of various diseases. The pineapple plant or (Ananas comosus (L) Merr) is one of the plants that is often used for treatment. Pineapple (Ananas comosus (L) Merr) contains flavonoids and phenolics, which are productive as natural antioxidants. This research was carried out using experimental methods. The research included collecting materials followed by plant identification, phytochemical screening, making ethanol extract from pineapple peel, and testing antioxidant activity using the radical scavenger method using a Visible Spectrophotometer. The results of research on pineapple rind Simplicia (Ananas comosus (L) Merr), ethanol extract, and water juice of nans rind contain chemical compounds of alkaloids, flavonoids, tannins, saponins, steroids/triterpenoids and glycosides. Ethanol extract and water juice from pineapple peel have antioxidant activity, which was tested using the radical scavenger method against DPPH (1,1-diphenyl-2-picryhydrazyn) solution. Ethanol extract and water juice from pineapple peel have antioxidant activity, but unlike vitamin C, the antioxidant is categorized as very strong. Meanwhile, the ethanol extract of pineapple peel is categorized as strong, and the water extract of pineapple peel is categorized as medium.